HUBUNGAN CUACA DAN KONSENTRASI PM10 (STUDI KASUS DI KOTA BANJARBARU) - Miftahul Munir; Arief R. M. Akbar; Badaruddin Badaruddin; Raiwani Wahdah (Universitas Lambung Mangkurat, 2018)
This research’s aim was to identify the relationship between weather element with PM10 concentration in Banjarbaru both during normal condition and during smoke fog (smog) condition, to study the condition’s effect afflicts to weather element and PM10 concentration in ambient air and to determine standard quality concentration PM10’s threshold in ambient air during smog condition. The data were 10 minute PM10, humidity, and temperature and daily weather of 2015 that obtained from Banjarbaru Climatology Station meanwhile data of hotspot’s in South Kalimantan at 2015 was taken from MODIS satellite of Terra Aqua owned by NOAA. The 10 minutes data has been clustered using K-means method and the daily weather element relationship with PM10 concentration obtained based on regression analysis. When normal conditions, only temperature, and duration of irradiance were significantly has positively correlated with PM10 concentration, air humidity and significant rainfall are negatively correlated, the remain is not significant in effect, while during smog conditions; temperature, duration of irradiation, air pressure, average wind velocity, and maximum significant wind speed are positively correlated, air humidity, and rainfall significantly negatively correlated. Based on the results of K-means clustering analysis of PM10 concentration, there was higher humidity, higher temperature, and PM10 concentrations were below the standard quality threshold under normal conditions while in the case of smog conditions, lower humidity, lower temperature, and PM10 concentrations were above the quality standard threshold. PM10 concentration during smog condition reaches dangerous status/above the standard quality threshold before dry season until late dry season at 02.20 is in the dusk until 12.30 pm.